Comparison of the Effectiveness of Google Ads and Facebook Ads as Promotional Media with the Epic Model at Four Points By Sheraton Bali, Kuta - Ni Kadek Mita Dewi; I Gusti Ngurah Sanjaya; Gede Sedana Wibawa Yasa (LPPM Institut Studi Islam Sunan Doe, 2024)
As a 4* hotel in Bali, Four Points by Sheraton Bali, Kuta uses various media to advertise. The number of advertising promotion media used, it is necessary to compare the effectiveness of similar advertising media. The purpose of this research is to compare the effectiveness of Google Ads and Meta Ads as promotional media for Rediscover Kuta at Four Points by Sheraton Bali, Kuta. This research method is a quantitative descriptive research with the EPIC Model approach. The sampling technique used was non-probability sampling with a purposive sampling technique with a total of 96 respondents, namely internet users aged 21 to 65+ years who have seen at least once Facebook Ads and/or Google Ads posted by Four Points by Sheraton Bali, Kuta. Of the 96 respondents, 44 saw Google Ads ads and 52 respondents knew Facebook Ads information. Data was taken by distributing questionnaires in the form of questionnaires. The results of this study indicate that both Google Ads and Facebook Ads promotional media are considered effective, but Facebook Ads gets a higher EPIC Rate, which is 3.23 compared to Google Ads with an EPIC Rate of 3.06. Meanwhile, after being tested with the Independent t-test, the two did not have a significant difference. This proves that these two promotional media are effectively used.